Human geography - Tredinnick, Kyle (--For dummies, 2024)
Human geography is the study of how people move around--within communities, across cultures, and around the world. If you're taking a human geography class or looking for a better understanding of our world, this Dummies guide has got you covered. Written in plain-English, this book tracks concepts covered in an introductory course, such as migration patterns, agriculture, political borders, and environmental issues. Clearer than a textbook and more interesting than an online article, this is the human geography resource you need.-- Back cover.